FLYING WITHOUT WINGS: STORIES OF NON-PHYSICAL EDUCATION GRADUATES TEACHING PHYSICAL EDUCATION - Bucao, Kirk Nicolas; Robledo, Elamae; Galaura, Lenziel L. (European Journal of Physical Education and Sport Science, 2024)
The purpose of this study is to determine how non-physical education graduates who have physical education as their teaching load perceive their everyday teaching performance, knowing that it is not their field of specialization. This study will help us understand how they cope with the teaching challenges, knowing that their situation is aligned with the rampant job mismatches in the Philippines. This study will cover the stories of a non-physical education graduate teaching physical education, everyday challenges, teaching performance, resolution, and support from the school and others. This study is a qualitative research study. The respondents of this study are not physical education graduates, but they teach physical education in their schools. In this study, the researchers used a researcher-made instrument to assess the data, and then the researchers proceeded to analyze the data using the coding procedures. Upon conducting the study, the researcher found that this study proves that a non-physical education graduate who teaches physical education experienced significant circumstances in teaching the subject.  Article visualizations: